KONSEP DISTRIBUSI DAN BASE VALUE SISTEM EKONOMI ISLAM - Samsuduha, St (Universitas Muslim Indonesia, 2021)
This paper reviews the concept of distribution and the base value of the Islamic economic system. These two themes are interrelated discourses with one another. As understood, the Islamic economic system aspires to an economic order that is just and beneficial for human life. Therefore, distribution as one of the market instruments in the economic world must effectively take place in the corridor of positive and fair values. The results of the study in this paper concluded that; First, distribution in economic studies is a system of distributing goods and services from producers to consumers. This process is a stage that takes place to synchronize the stages of production of goods with sales. Distribution is an important aspect that determines the adequacy of goods needs in the community. Therefore, the balance can be maximized through the selection of distribution channels in an effective, fair and sustainable manner. Second, the Islamic economic system provides a basic value formulation that can be used as a benchmark in the distribution process. Thus, the distribution made must be in line with the basic value of ownership; the basic value of freedom; basic values of justice; basic value of balance; and the value of togetherness.Â